EFEKTIVITAS BERBAGAI RASIO KOMBINASI PAKAN KOMERSIAL DAN TEPUNG WORTEL TERHADAP KECERAHAN WARNA DAN PERTUMBUHAN IKAN MAS KOKI (Carassius auratus) - Kadek Ade Sutawan; Alexander Korinus Marantika; Made Dwipa Kusuma Maharani (Universitas Mataram, 2026)
Goldfish (Carassius auratus) is an ornamental fish commodity with high economic value, whose market price is significantly influenced by visual quality, particularly color brightness. This study aimed to analyze the effect of adding carrot meal (Daucus carota) to commercial feed on the color brightness and growth of goldfish, as well as to determine the most optimal dose. The research was conducted for 60 days in Tukadmungga Village, Buleleng Regency, Bali, using a Randomized Block Design (RBD) with four treatments and three replications. The treatments administered were A (100% commercial feed), B (85% commercial feed + 15% carrot meal), C (80% commercial feed + 20% carrot meal), and D (75% commercial feed + 25% carrot meal). The observed parameters included color brightness, absolute growth in length and weight, specific growth rate (SGR), feed conversion ratio (FCR), survival rate (SR), and water quality. Data were analyzed using ANOVA at a 95% confidence level, followed by Duncan's multiple range test. The results showed that the addition of carrot meal had a significant effect on improving the color brightness of goldfish (P < 0.05), with the highest increase observed in treatment D at 0.73 ± 0.08. However, treatments C (20%) and D (25%) were not significantly different; thus, the 20% dose was considered optimal. The addition of carrot meal did not significantly affect growth, SGR, or FCR (P > 0.05). The survival rate ranged from 87–100%, and water quality remained within the optimal range. Carrot meal has the potential to be used as a natural source of carotenoids to enhance the color brightness of goldfish without compromising growth and feed efficiency.